The Relationship Between Cardio-Respiratory Endurance (Vo2max) and Student Achievement - I Komang Ragil Palguna; I Ketut Yoda; I Ketut Iwan Swadesi (Jurnal Muara Olahraga, 2026)
This study aimed to examine the relationship between cardiorespiratory endurance (VO₂max) and Physical Education, Sports, and Health (PJOK) learning outcomes among tenth-grade students of SMKN 3 Singaraja in the 2025/2026 academic year. This study employed a quantitative correlational design involving 74 students from the Visual Communication Design (DKV) program. Cardiorespiratory endurance was estimated using a 2.4 km running test, while PJOK learning outcomes were obtained from students’ final semester grades. Data were analyzed using the Pearson Product Moment correlation after meeting the normality assumption. The results revealed a significant positive relationship between VO₂max and PJOK learning outcomes (r = 0.242, p < 0.05), indicating a low correlation. The coefficient of determination showed that VO₂max contributed 5.86% to the variation in PJOK learning outcomes. It can be concluded that better cardiorespiratory endurance tends to be associated with better PJOK learning outcomes, although its contribution is relatively small.